2014
DOI: 10.1063/1.4890358
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic behavior of NiCu nanowire arrays: Compositional, geometry and temperature dependence

Abstract: Arrays of Ni 100Àx Cu x nanowires ranging in composition 0 x 75, diameter from 35 to 80 nm, and length from 150 nm to 28 lm have been fabricated by electrochemical co-deposition of Ni and Cu into self-ordered anodic aluminum oxide membranes. As determined by X-ray diffraction and Transmission Electron Microscopy, the crystalline structure shows fcc cubic symmetry with [111] preferred texture and preferential Ni or Cu lattice depending on the composition. Their magnetic properties such as coercivity and squaren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 37 publications
1
7
1
Order By: Relevance
“…1 b.1), the H c and m r decease, presenting similar values in both directions. However even for the smallest aspect ratios (lower than 1) our results evidence the existence of an easy magnetization axis along the parallel direction for all samples, contrary to the reported in the literature 41 , 42 . This behavior can be attributed to the high dipolar interactions exhibited between the neighbor Ni segments 43 .…”
Section: Resultscontrasting
confidence: 99%
“…1 b.1), the H c and m r decease, presenting similar values in both directions. However even for the smallest aspect ratios (lower than 1) our results evidence the existence of an easy magnetization axis along the parallel direction for all samples, contrary to the reported in the literature 41 , 42 . This behavior can be attributed to the high dipolar interactions exhibited between the neighbor Ni segments 43 .…”
Section: Resultscontrasting
confidence: 99%
“…3, it can also be seen that the H C , as well as the M r /M s , decreases with increasing l. We also observed that the H C and M r /M S were significantly influenced by varying the d of the nanowire. Similar results have been reported in multisegment nanowires such as CoNiP [36], Ni/Cu [37], NiCu/Cu [39], Co/Ni [40], Co/Fe [41], and Ni/Fe [42].…”
Section: The Influence Of the Geometrical Parameters On The Hysteresisupporting
confidence: 87%
“…Because MNs show novel and interesting properties with a specific structure, they have been studied to investigate the dependence of geometrical parameters such as the wire diameter [36][37][38], segment thicknesses [28,[37][38][39][40][41][42], and aspect ratio [43,44] on the magnetic properties. Moreover, the hysteresis properties of the Ising-type multisegment nanowire with alternating magnetic spin-1/2 and spin-1 segments were investigated by using the EFT with correlations.…”
Section: Introductionmentioning
confidence: 99%
“…So far, single element, binary alloy, ternary alloy and multilayered magnetic NWs such as Co, Ni, Fe, NiCu, FeCo, CoCu, CoNi, FeCoCu and CoNi/Cu have been prepared using the electrodeposition technique [12][13][14][15][16][17][18][19][20]. Having paid particular attention to both the binary alloy and multilayered NWs due their potential application in the magnetoresistive and thermoelectric devices at the nanoscale, they show considerable amounts of magnetoresistance and magnetothermopower, which in turn, can compete with those of the conventional counterpart materials [18,20,21].…”
Section: Introductionmentioning
confidence: 99%